Pengembangan LKPD berbasis Problem Based Learning pada Materi Benzena dan Turunannya untuk Kelas XII SMA/MA - Nurwahyuni Nurwahyuni; Suryelita Suryelita (Entalpi Pendidikan Kimia, 2023)
Benzene and its derivatives are aromatic compounds studied on the second semester of grade XII SMA/MA. Structure, nomenclature, physical properties, chemical reactions, uses and harmful and harmless benzene derivatives are the material studied on this topic. In the discussion of this material has interconnected regularities. Problem-Based Learning (PBL) is one of the learning models used to study this material. Producing student worksheet-based PBL and determining the validity categories were the purposes of this study. 4-D models (define, design, develop, disseminate) were used in this study. This study is limited to the develop stage, namely the validity test. The product was validated by 3 chemistry lecturers from FMIPA UNP and 2 chemistery teachers at SMAN 1 Koto Baru Dharmasraya. The instrument validity questionnaire was analyzed by using the Aiken V formula. The results of the analysis revealed that the developed LKPD was “very valid” resulting 0,85.